A unique perihilar renal vascular variation with fenestrated left renal vein: a case report - Philip, Shalom Elsy; Nallathampy, Rani (International Journal of Research in Medical Sciences, 2025)
Each kidney is supplied by one renal artery and one renal vein which arises as a lateral branch of abdominal aorta and inferior vena cava respectively between the upper and lower margins of the first and second lumbar vertebrae. Here we report a case of fenestrated left renal vein, retro aortic vein and renal artery variation in a left-sided kidney emphasizing clinical, functional, and embryological perspectives of renal vascular variation. Precise knowledge of renal vascular anatomy and its variations are essential to prevent complications during surgical interventions, especially during kidney transplantation.